2023
DOI: 10.3390/cancers15061694
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic Systems and Cancer: Focus on Tachykinin and Calcitonin/Calcitonin Gene-Related Peptide Families

Abstract: The roles played by the peptides belonging to the tachykinin (neurokinin A and B) and calcitonin/calcitonin gene-related peptide (adrenomedullin, adrenomedullin 2, amylin, and calcitonin gene-related peptide (CGRP)) peptide families in cancer development are reviewed. The structure and dynamics of the neurokinin (NK)-2, NK-3, and CGRP receptors are studied together with the intracellular signaling pathways in which they are involved. These peptides play an important role in many cancers, such as breast cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 359 publications
0
11
0
Order By: Relevance
“…Our future studies will address these knowledge gaps. The findings of decreased endothelial cells in the lungs of LPS-exposed Adm-haplodeficient (Adm +/− ) mice reconfirm the proangiogenic effects of Adm [43][44][45]47,[105][106][107][108] and the importance of endothelial cell health in mitigating BPD [12,13,70]. Type II pneumocytes play a vital role in BPD pathogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…Our future studies will address these knowledge gaps. The findings of decreased endothelial cells in the lungs of LPS-exposed Adm-haplodeficient (Adm +/− ) mice reconfirm the proangiogenic effects of Adm [43][44][45]47,[105][106][107][108] and the importance of endothelial cell health in mitigating BPD [12,13,70]. Type II pneumocytes play a vital role in BPD pathogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…Numerous studies have indicated increased serum CGRP levels in breast, lung, thyroid, and prostate cancers [14,[35][36][37][38][39]. However, the data in the literature related to the tissue expression of CGRP in the normal and tumor colon are practically non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin [83] and oxaliplatin also stimulate TRPV1 expression [84] (along with TRPA1 [84] and TRPM8 [85]) in sensory afferents. TRPV1-expressing nerve endings release calcitonin gene-related peptide (CGRP) that, in turn, can stimulate cancer growth [73][74][75]. In a murine cancer model (Lewis carcinoma inoculated into the paw), tumor growth was attenuated in both TRPV1-null and αCGRP-null mice compared to in wild-type littermates [76].…”
Section: Trpv1 In Cancer Pain: Molecular Mechanismsmentioning
confidence: 99%